2015
DOI: 10.1002/jcc.23870
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical comparative studies on transport properties of pentacene, pentathienoacene, and 6,13‐dichloropentacene

Abstract: Pentacene derivative 6,13-dichloropentacene (DCP) is one of the latest additions to the family of organic semiconductors with a great potential for use in transistors. We carry out a detailed theoretical calculation for DCP, with systematical comparison to pentacene, pentathienoacene (PTA, the thiophene equivalent of pentacene), to gain insights in the theoretical design of organic transport materials. The charge transport parameters and carrier mobilities are investigated from the first-principles calculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 89 publications
(139 reference statements)
1
14
0
Order By: Relevance
“…. This order of magnitude agrees with other results presented in the literature 15,16,20,42,43 . Moreover, it is worthwhile to stress that intrinsic charge mobility is difficult to obtain experimentally.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…. This order of magnitude agrees with other results presented in the literature 15,16,20,42,43 . Moreover, it is worthwhile to stress that intrinsic charge mobility is difficult to obtain experimentally.…”
supporting
confidence: 93%
“…Recently, Zhang and colleagues have theoretically investigated the charge transport parameters and carrier mobilities in pentacene and pentathienoacene (PTA) crystals within the framework of Marcus' semi-classical theory and quantum nuclear tunneling model, coupled with random walk simulation 15 . In their work, a systematic comparative study was also carried out for pentacene and PTA to gain insights into the theoretical design of these materials.…”
mentioning
confidence: 99%
“…As DCP has a similar chromophore to pentacene, the optical transition dipole moment of DCP aligns with the molecular short-axis. 27,33,34 That is, the optical transition dipole moment of DCP has the same direction as the collective vibrations along M-axis, and forms an angle of ~65° with X-axis (the long-axis of nanobelt). Therefore, the intramolecular exciton-phonon coupling is stronger along the M-axis and leads to larger resonant effects for the 1361 cm -1 mode.…”
Section: Resultsmentioning
confidence: 99%
“…25,26 Both experimental and calculated results have shown that the existence of large π-π overlap between adjacent molecules in DCP nanobelts leads to highly anisotropic carrier transport in bulk DCP crystals. 26,27 Together with the good ambient stability as well as the easy syntheses and purification, DCP presents itself as an ideal candidate for studying the anisotropic coupling of exciton and molecular vibrations, which is fundamentally important for understanding the interaction between light and organic semiconductors at molecular scale.…”
Section: Introductionmentioning
confidence: 99%
“…where V eff is the effective electronic coupling, and k B is Boltzmann constant, and λ is the reorganization energy. Though band model and hopping model are two widely used methodologies to explain charge transport mechanism in organic semiconductors, the later is often used near room temperature in the cases of localized charge carriers with intermolecular electron coupling being far less than the electron‐vibration coupling ,,,,,…”
Section: Introductionmentioning
confidence: 99%